Fa’aliyat TathbIq Lu’bah Froggy Jump li Tarqiyah Ta’lim Maharat al-Qira’ah: bahtsu Tajribiy/The Effectiveness of Using Froggy Jump Game to Improve Reading Skills: An Experimental Study - Via Aulia; Mu'at Mu'at (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
The